PENGARUH PENGUMUMAN PEMBELIAN KEMBALI SAHAM (BUY BACK) TERHADAP RESPON PASAR: STUDI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Muhammad Luky Junizar; Aditya Septiani (Diponegoro Journal of Accounting, 2013)
This study aims to determine the effects of the buy-back announcement to the market response at the companies listed in the Indonesian Stock Exchange under the regulation of Bapepam-LK No. XI.B.3 XI.B.2 on the buy-back procedure. This study uses the average daily abnormal return and the average daily trading volume activity to confirm that the information from the buy back announcement has significant effects to the market. This study also uses the average cumulative abnormal return and trading volume activity to investigate differences in cumulative abnormal returns and trading volume activity before and during the buy-back announcement. The study population was all the companies which performed buy back actions during 2008-2012. The research samples are 20 announcements. Data were analyzed using T-test and Paired Sample Test/Wilcoxon-Signed Rank Test. Calculation of expected return uses the market model utilizing a simple OLS regression (Ordinary Least Squares). The results show that buyback announcements have significant effects and there are differences in the average cumulative abnormal return before and after the announcement of the buy-back. In addition, information on buy back announcement significantly influences on the volume of trading activity, there are differences in the average trading volume activity before and during the transaction in progress.